Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.166
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Degree Splitting, Edge Coloring, and Orientations

Abstract: We study a family of closely-related distributed graph problems, which we call degree splitting, where roughly speaking the objective is to partition (or orient) the edges such that each node's degree is split almost uniformly. Our findings lead to answers for a number of problems, a sampling of which includes:• We present a poly log n round deterministic algorithm for (2∆−1)·(1+o (1) • We show that sinkless orientation-i.e., orienting edges such that each node has at least one outgoing edge-on ∆-regular graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 29 publications
0
92
0
Order By: Relevance
“…They also exhibited an O(log log n) round randomized algorithm and an O(log n) round deterministic algorithm for ∆-coloring trees, hence proving that these complexities are tight and they have an exponential separation. Ghaffari and Su [GS17] later showed that the original problem of sinkless orientation (which is a special case of the Lovász Local Lemma) also exhibits the same exponential separation, by providing a Θ(log log n)-round randomized and a Θ(log n)-round deterministic algorithm for it. We emphasize that this exponential separation is between complexities that are in O(log n).…”
Section: An Overview Of the Recent Developments On Det Vs Randmentioning
confidence: 99%
“…They also exhibited an O(log log n) round randomized algorithm and an O(log n) round deterministic algorithm for ∆-coloring trees, hence proving that these complexities are tight and they have an exponential separation. Ghaffari and Su [GS17] later showed that the original problem of sinkless orientation (which is a special case of the Lovász Local Lemma) also exhibits the same exponential separation, by providing a Θ(log log n)-round randomized and a Θ(log n)-round deterministic algorithm for it. We emphasize that this exponential separation is between complexities that are in O(log n).…”
Section: An Overview Of the Recent Developments On Det Vs Randmentioning
confidence: 99%
“…Edge splitting (also known as degree splitting) can be defined as coloring all edges red or blue such that each node has at most ∆ 2 (1 + ε) edges in each color. Ghaffari and Su [GS17] provided a poly log n-round algorithm for edge-splitting, which led to the first efficient deterministic distributed 2∆(1 + o(1))-edge-coloring algorithm, thus partially resolving Open Problem 11.4 of [BE13]. A significantly more efficient edge splitting algorithm was later provided in [GHK + 17b].…”
Section: The Splitting Problem and Its Significancementioning
confidence: 99%
“…Due to the observation of (27), X u i and X v i are mutually independent. According to the exponential correlation of (29), by choosing a suitably small t = O(log n), the total variation distance between (σ u i , σ v i ) and (…”
Section: Lower Boundsmentioning
confidence: 99%
“…For the σ ′ returned by a t-round protocol where t ≤ 0.49 · diam(G), according to the property (27), the σ ′ Gx and σ ′ Gy are independent of each other, thus the phases of G x and G y on σ ′ are independent of each other: …”
Section: Proof Of the ω(Diam) Lower Boundmentioning
confidence: 99%
See 1 more Smart Citation